POLITICAL DYNAMICS AND POLICY IMPLICATIONS OF INDONESIA-AUSTRALIA BORDER MANAGEMENT - Lutfie, Ratu Zahirah; Suharjimantoro, Suharjimantoro (Universitas Padjadjaran, 2025)
This study offers a political science analysis of border management policies in Indonesia and Australia, focusing on security, community welfare, and international relations. Indonesia adopts a development-oriented approach aimed at enhancing infrastructure and economic access in border areas, promoting national integration but facing coordination and surveillance challenges. Australia, in contrast, implements a security-driven approach, particularly through Operation Sovereign Borders, effectively preventing illegal immigration yet criticized for its stringent, less humanitarian stance. Employing qualitative methods, including literature review and online media analysis, this study examines the political implications and geopolitical context of each policy. Findings suggest that Indonesia could enhance border security by integrating advanced technology, while Australia might benefit from a more cooperative, humanitarian approach to improve regional relations. This analysis contributes to political science discussions on border governance, proposing a balanced model that addresses both security and welfare in managing national borders.